UNDERSTANDING THE STUDENT HEARING DIFFICULTIES TOWARD NATIVE AND NON-NATIVE SPEAKER ACCENT IN L2 LISTENING ASSESSMENT - Solihah, Bakiyatus; Retnaningdyah, Pratiwi; Purwati, Oikurema; Anam, Syafi’ul (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
The accent is one of the characteristic forms of the language used for communication when outside or inside the language learning classroom, then understand difficulty listening to students through the Native and Non-Native Speaker Accent in L2 in the listening assessment requires a more thorough investigation. The purpose of this study to explore how extent students can understand native and non-native speakers with different accents and how they perceive about hearing difficulties toward Native speaker accent and Non-native speaker accent. This research focuses on 12th graders majoring in hospitality at state vocational high school in Bangkalan, Madura. The research data were collected through observation and interviews. The results of this study show that the clarity, speed and accent of native and non-native speakers (American) and non-native speakers (Indonesian) become difficulties and barriers for students to understand and complete their listening tasks. This is because they are used to hearing accents from non-natives speakers rather than accents from native speakers. Furthermore, when students took the American Accent English Test compared to the Indonesian Accent English Test, all scores were much lower